Developing items using by pilot test, confirmatory factor analysis statistical in literacy for communication and supervision clinical elements provider - Saleh, Nor Shela; Yaacob, Hashim Fauzy; Mohd Shafie, Rosli (MCSER Publishing, 2015)
This research about the communication and supervision developments as an element in the future set of questionnaire. The set of questionnaire aspect need regarding medical learning of trainee doctor. The selected of two elements based on previous research, the theory and model support the importance of both. The researcher also use several of set a questionnaire from previous of research as adaptation process to create the elements and further the strength by validity testing via experts of study. A number of samples selected as respondents are 222 from 250 number of population. Referring on research objective achievement, the number of items has been changed after validity test. For the reliability test, all items after validity test selected are accepted. The confirmatory factor analysis has been shown that two items from communication elements and two items from supervision have been rejected. The final decision numbers of items in communication elements are eight, while in supervision are 12 items.